A review on electrocatalytic oxidation of methane to oxygenates. Issue 31 (21st July 2020) - Bagherzadeh Mostaghimi, Amir Hassan; Al-Attas, Tareq A.; Kibria, Md Golam; Siahrostami, Samira
Abstract : Methane, the main component in natural gas, is widely utilized for energy consumption and production of important chemicals. Abstract : Methane, the main component in natural gas, is widely utilized for energy consumption and production of important chemicals. However, existing industrial processes for (direct or indirect) production of chemicals from methane are capital-, energy-, and carbon-intensive. Alternatively, electrochemical partial oxidation of methane to high-value fuels and feedstocks is gaining momentum globally due to its modular design, adaptability with intermittent renewable energy, and operation in a wide range of temperatures and pressures. As the prices of renewable electricity continue to drop, the electrochemical pathway for methane valorization can potentially compete with century-old conventional processes if the target performance metrics can be achieved at scale. Herein, we review the recent advances in electrochemical partial oxidation of methane to high-value fuels and feedstocks, with a focus on mechanistic understanding and reaction engineering, i.e., the effect of temperature, pressure, electrolyte, pH and reactor design. We conclude with some perspectives on the future development of this key research front.